Redox-active monolayers in mesoporous silicon - Ciampi, S.; Guan, B.; Darwish, Nadim; Reece, P.; Gooding, J. (American Chemical Society, 2012)
Herein, redox reactions at chemically derivatized porous silicon (PSi) films are investigated. Passivation of the PSi matrix, by replacing metastable Si-H termini with nonpolar Si-C=C-R linkages, allows the electrochemical PSi device to operate in aqueous environments under oxidizing conditions (i.e., electron hole accumulation regime). Cu(I)-catalyzed alkyne-azide cycloaddition reactions are used to anchor ferrocene derivatives and probe electrochemical reactions at the exceedingly large surface area-to-volume ratio of mesoporous PSi. The forward-biased p-type PSi/electrolyte interface retains a quasi-metallic behavior throughout its entire contour, and it does so for prolonged times even when the electrode is poised at potentials at which a bare silicon electrode would rapidly oxidize. The interfacial capacitance of the PSi matrix is, however, unexpectedly low. An explanation is proposed where PSi morphology and the semiconductor space-charge layer capacitance play a significant role in determining the charging properties of the electrode. These results are important for the application of porous semiconductor electrodes in sensing, electrocatalytic, and energy-conversion devices.